A general look at the handling of solid waste (2019)
The technological advance that brought us the modern world has contributed to having thousands of amenities in the world population in general, as a result of that we have become consumer goods and services demanding the mass production of products that meet certain needs, without keep in mind the environmental damage that this may impact because at the time these benefits are made, solid waste is also produced, which is commonly known as garbage, causing a problem at the time of treatment of this waste, worldwide we see how There are already countries that solved this problem by promoting the regulations for this, in the same way at the national level a series of regulations has been created but these are far from the real solution because when implementing landfills, their useful life was not taken into account. In a very short time there will be no where to deposit our waste, by its side the entities territo rials are more aware of this problem and, from now on, new techniques are being proposed, from the separation at the source to the reach of new technologies as they already have in other more developed countries.